Fulminant Haemolysis Following Endoscopic Retrograde Cholangiopancreatography - Bibi, M (2021)
We report the case of a 77-year-old-man with a history of type 2 diabetes mellitus who underwent endoscopic retrograde cholangiopancreatography (ERCP) because of a gallstone in the common bile duct. Thirty-six hours after the procedure, the patient developed persistent fever and epigastric pain associated with de novo jaundice. Massive haemolysis (with exuberant spherocytosis) occurred and patient died in 3 hours. Clostridium perfringens was isolated in the blood cultures. Massive haemolysis associated with C. perfringens has a high mortality rate. Management involves a high index of suspicion after gastrointestinal procedures like ERCP, surgical consultation, antibiotic therapy, transfusion of red cell concentrates and, potentially, hyperbaric oxygen therapy. Learning points: Endoscopic retrograde cholangiopancreatography (ERCP) can be complicated by Clostridium perfringens bacteraemia with devastating consequences.C. perfringens infection should be suspected in an icteric, febrile patient with abdominal pain, especially if intravascular haemolysis is present.Management of intravascular haemolysis and inflammation in a patient following ERCP should be multidisciplinary, involving surgery when needed and potentially hyperbaric oxygen therapy; penicillin or penicillin-derived antibiotics associated with clindamycin or metronidazole are the mainstays of antibiotic therapy.